1990
DOI: 10.1111/j.2044-8325.1990.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and perceived power in manager—subordinate relations

Abstract: A field study in three organizations investigated gender differences in subordinates' perceptions of managers' power. For 55 female and 55 male managers matched on position power, one subordinate per manager (N = 110, half male and half female) completed a questionnaire. Perceived reward, legitimate, expert and referent power were all intercorrelated, but unrelated to coercive power. Male and female managers did not show the expected differences in combined, reward, coercive, legitimate and referent power. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Without specific information about the other three power bases, subjects made specific attributions about the power of the manager in the vignette, which would follow from attribution theory (e.g., Heider, 1958;Kelley, 1973). This would also explain why some of the scale intercorrelations reported in this study were higher than have been previously reported in the literature (Hinkin & Schriesheim, 1989;Ragins, 1989;Ragins & Sundstrom, 1990).…”
Section: Suggestions For Future Researchmentioning
confidence: 58%
See 1 more Smart Citation
“…Without specific information about the other three power bases, subjects made specific attributions about the power of the manager in the vignette, which would follow from attribution theory (e.g., Heider, 1958;Kelley, 1973). This would also explain why some of the scale intercorrelations reported in this study were higher than have been previously reported in the literature (Hinkin & Schriesheim, 1989;Ragins, 1989;Ragins & Sundstrom, 1990).…”
Section: Suggestions For Future Researchmentioning
confidence: 58%
“…The power bases correlated significantly with each other, which suggests that the French and Raven bases of power are not completely orthogonal constructs. Other studies have also found significant patterns of intercorrelations between measures of the French and Raven's power bases (e.g., Frost & Stahelski, 1988;Hinkin & Schriesheim, 1989Ragins, 1989;Ragins & Sundstrom, 1990).…”
Section: Scale Intercorrelationsmentioning
confidence: 88%
“…In the past, researchers have attempted to measure the overall power of a source by simply adding together ratings of the five individual French and Raven (1959) power bases (Ragins, 1989(Ragins, , 1991Ragins & Sundstrom, 1990;Stahelski & Patch, 1993). The results of this study demonstrate that this practice is not appropriate.…”
Section: Discussionmentioning
confidence: 91%
“…We have no independent verification that the power relationships reported by the graduate students are veridical. Other researchers have, in fact, examined power relationships from multiple perspectives (e.g., Ragins & Sundstrom, 1990). However, it has been proposed that the perception of the individual's power is important in determining the person's actual power (Tedeschi, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation